Intensi Berwirausaha Mahasiswa Ditinjau dari Sikap, Norma Subjektif, dan Persepsi Kontrol Perilaku - Sri Utami (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study analyzes the effects of attitude toward entrepreneurship, subjective norms, and perceived behavioral control on students' entrepreneurial intention. The study used a quantitative explanatory design involving 205 students from the Department of Accounting Science, Universitas Negeri Makassar. Respondents were selected through purposive sampling based on three criteria: active student status, completion of an entrepreneurship course, and willingness to complete the questionnaire. Data were collected using a closed-ended questionnaire with a five-point Likert scale and analyzed using multiple linear regression. The results show that attitude toward entrepreneurship has a positive and significant effect on entrepreneurial intention (β = 0.203; p < 0.001), subjective norms have a positive and significant effect (β = 0.212; p < 0.001), and perceived behavioral control has a positive and significant effect (β = 0.382; p < 0.001). Together, the three variables explain 45.6% of the variance in entrepreneurial intention. Perceived behavioral control is the strongest predictor, indicating that students' entrepreneurial intention is closely related to confidence in managing business tasks, risks, and opportunities.